Female sexual pain: Epidemiology and genetic overlap with chronic widespread pain. (30th May 2017) - Burri, A.; Ogata, S.; Williams, F.
Abstract: Background: Increased tender spots and lowered general pain thresholds have been observed in patients with dyspareunia. Based on this, the aim of the study was to compare the co‐occurrence of female sexual pain across various pain populations and to further explore the aetiological structure underlying sexual pain by dissecting the genetic and environmental covariation among sexual pain, chronic widespread pain (CWP) and the previously reported psychological correlates of anxiety sensitivity and depression. Methods: A multivariate twin study including 1489 female twin individuals (246 full MZ pairs, 187 full DZ pairs and 623 whose co‐twin did not participate). Main outcomes measures included self‐reported diagnosis of osteoarthritis and rheumatoid arthritis, and validated questionnaires for the assessment of sexual pain, CWP, depression and anxiety sensitivity. Results: Sexual pain showed a small but statistically significant correlation with CWP ( r  = 0.08; p  < 0.05), anxiety sensitivity ( r  = 0.15, p  < 0.001) and depression ( r  = 0.09, p  < 0.01). The heritability of sexual pain was found to be 31%. Multivariate variance component analysis revealed a genetic factor common among CWP, depression, anxiety sensitivity and sexual pain, and a second genetic factor shared between anxiety sensitivity and sexual pain only. We further detected genetic and environmental factors unique to sexual pain, explaining 24.01% and 67.24%, respectively, of the phenotypic variance. Conclusions: Our findings suggest some overlap between sexual pain and CWP and point towards a shared but complex psychophysiological aetiology underlying sexual pain. Results further highlight the influence of specific environmental and contextual stressors in the development and maintenance of sexual pain. Significance: Sexual pain shares a common genetic aetiology with chronic widespread pain and the frequently reported psychological comorbidities of depression and anxiety. Overall this suggests a complex psychophysiological aetiology underlying chronic pain conditions. The high proportion of variance in sexual pain explained by environmental factors further highlights the importance of specific environmental and contextual stressors in the development and maintenance of the condition.